Calcium homeostasis and certain aspects of its disturbances in juvenile idiopathic arthritis - Yu.G. Antypkin; Yu.V. Marushko; L.I. Omelchenko; O.M. Mukvich; T.A. Liudvik; N.Yu. Bondarenko; O.A. Bovkun; D.L. Ismakaieva (Zaslavsky O.Yu., 2022)
Background. In the pathogenesis of juvenile idiopathic arthritis (JIA), the main role is played by immunopathological changes in the body with a loss of tolerance to the elements of own tissues; herewith, disorders of calcium and bone metabolism are very important. Such changes occur as a result of autoimmune inflammation, pharmacotherapy, and the influence of a number of other factors that negatively affect calcium homeostasis in the body. Purpose: to study the features of calcium homeostasis and certain aspects of its disorders with an assessment of the structural and functional state of bone tissue, taking into account clinical subtypes and disease activity. Material and methods. Sixty-two children with JIA aged 3.5 to 16 years were examined, of them 11 had systemic and 51 had oligo- and polyarthritis. There were determined serum concentrations of a total calcium using the Lachema test kit (Czech Republic), protein-bound and ultrafiltered fractions, content of inorganic phosphorus (with the generally accepted spectrophotometric method using the Cobas 6000 analyzer and test systems by Roche Diagnostics, Switzerland), the activity of total alkaline phosphatase and its isoenzymes (bone and intestinal) using the Lachema test system (Czech Republic). Ultrasonic osteometry of the calcaneal (trabecular) bone was performed on the Achilles device (Lunar, USA). Results. A significant decrease was found in the average concentration of total calcium, protein-bound calcium in systemic JIA and in high disease activity. The concentration of the ultrafiltered calcium fraction decreased only with high disease activity. The average concentration of inorganic phosphorus in children with oligo- and polyarthritis was within the normal range, while in systemic JIA it decreased. A significant decrease in the serum content of inorganic phosphorus, as well as in the activity of total alkaline phosphatase and its bone isoenzyme was detected in patients with high activity of systemic JIA. In patients with JIA (oligo-, polyarthritis) characterized by a slowly progressive rheumatic process, only the indicator of broadband ultrasound attenuation significantly changed during the first year of the disease, while the speed of ultrasound propagation and the index of bone tissue strength were not changed. In patients with a longer duration of the disease, all densitometric indicators decreased significantly. In the group of patients with systemic JIA and a rapidly progressive course, high activity of the disease that required a glucocorticoid therapy, a significant loss of bone mass was noted by the end of the first year of the disease. Conclusions. In JIA, there are changes in the concentration of total calcium and its protein-bound and ultrafiltered fractions in the blood serum, which indicate the tension of calcium-phosphorus metabolism and possible calcium deficiency in the body already at the early stages of the pathological process. A decrease in the activity of the alkaline phosphatase and its bone isoenzyme is associated with a violation of the structural and functional changes in the bone system of patients with JIA, which progresses with the duration of the disease. Patients with JIA require timely diagnosis and monitoring of calcium-phosphorus metabolism disorders with an assessment of the structural and functional state of the bone system for purposeful correction of comprehensive therapy due to the use of drugs in order to increase bone tissue regeneration, reduce the progression of osteopenia and osteoporosis, and preserve the health of the growing organism.